Apakah Sikap Bermazhab Berperan untuk Pengembangan Kesehatan Mental Remaja Muslim Nadhatul Ulama ? - Agoes Dariyo; Safrizal Safrizal; Ulfiah Ulfiah; Ujang Nurjaman (LPPM IAINU Kebumen, 2022)
This study aims to determine the relationship between mazhap attitudes and mental health in Muslim youth of Nadhatul Ulama. The technique of collecting data using a questionnaire is the attitude of the sect and mental health. The number of subjects involved in this study were 43 people (17-22 years, M = 19). Data analysis techniques with correlation and regression tests. It is known that there is a relationship between mazhab attitudes and mental health of Muslim youths of nadhatul ulama (r = .566, p = .000, p < .000). Likewise, it is known that the contribution of religious attitudes to mental health is 32%; and there are other factors by 68%. Furthermore, the results are discussed in this article.